Myocardial microvascular patterns in histological sections from patients with and without type 2 diabetes - Jaromír Šrámek; Aneta Pierzynová; Vojtěch Melenovský; Tomáš Kučera (PLoS ONE, 2026)
Type 2 diabetes is associated with small vessels dysfunction. This study assessed whether type 2 diabetes is associated with changes in the myocardial capillary pattern in two-dimensional histological sections as an indirect proxy for the three-dimensional network in the myocardium. We used myocardial samples from the left and right ventricles harvested during cardiac surgery (N = 53; 44 without and 9 with type 2 diabetes). We prepared histological sections with CD34-immunostained endothelium. We used cross-sections through the small vessels as points for two methods of point-pattern analysis: Voronoi-based analysis and fractal-based analysis. We were unable to detect differences in the microvascular pattern on myocardial sections of participants with and without type 2 diabetes.